Exploring the investment strategy of power enterprises under the nationwide carbon emissions trading mechanism: A scenario-based system dynamics approach. (May 2020) - Yu, Xianyu; Wu, Zemin; Wang, Qunwei; Sang, Xiuzhi; Zhou, Dequn
Abstract: This paper aims to explore the appropriate investment strategy for Chinese power enterprises with the effect of the nationwide carbon emissions trading (NCET) market. Based on the system dynamics (SD) theory and the analysis of investment strategies, the SD model for the investment analysis of power enterprises is proposed. The simulation experiments based on three different investment policy scenarios (i.e., conservative, neutral and active) are conducted. According to the simulation results, the reasonable short-term investment for enterprises should be increased. If enterprises choose to invest more resources in the installation of green powers (hydropower, wind power and photovoltaic), their carbon emissions and profits may be more difficult to achieve qualitative changes in the short term. It is suggested that before the establishment of NCET market, enterprises should give priority to investing in clean technology instead of large-scale green energy installation. In the long run, increasing the investment of green power generation will help enterprises resist the rising cost of carbon trading. In addition, even in the conservative policy environment, the enterprise can still achieve its carbon discharges peak value before 2030, so the government may consider adopting a loose policy standard to support the economic interests of power enterprises. Highlights: Different investment strategies of the power enterprise were clearly shown. A system dynamics model of investment was constructed. Carbon trading, carbon sinks and other measures were included in the model. The overlapping effects of different scenarios and policies were reflected. Specific investment implications were put forward for the power enterprise.